UPAYA PENINGKATAN HASIL BENIH PADI ORYZA SATIVA. L) PADA BERBAGAI TARAF GENANGAN AIR DAN TAKARAN VERMIKOMPOS DI LAHAN SAWAH IRIGASI ENTISOL - Nugrohotomo, Nugrohotomo; Yudono, Prapto; Syukur, Abdul (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2009)
The field research that was designed to study the effect of submerged level and vermicompost dosage to the quantity and quality of paddy seeds (Oryza sativa L) yield on irigated Entisol rice field was conducted from February 10